2016
DOI: 10.7754/clin.lab.2016.160512
|View full text |Cite
|
Sign up to set email alerts
|

Plasma Zonulin and its Association with Kidney Function, Severity of Heart Failure, and Metabolic Inflammation

Abstract: The inverse associations of zonulin with creatinine and markers of cardio-vascular risk (high CMLcalprotectin and kynurenine, low homoarginine) are novel findings that need further experimental and clinical clarification. Our study indicates zonulin involvement in metabolic inflammation in T2D, but no association with disease status in CHF.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
11
1
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 0 publications
2
11
1
3
Order By: Relevance
“…Furthermore we detected a significantly positive correlation between renal function, measured as eGFR, and the zonulin concentration and were thus able to confirm the finding recently reported by Dschietzig et al 14 In this study, which was conducted in a special group of patients with an auto matic implantable cardioverter/ defibrillator, the authors had described such a correlation for the first time, deducing that the low zonulin concentration associated with impaired renal function results from the depletion of zonulin with the urine. We were indeed able to determine a significantly nega tive correlation between the serum zonulin concentration and the extent of proteinuria measured as UACR in the urine.…”
Section: Discussionsupporting
confidence: 91%
“…Furthermore we detected a significantly positive correlation between renal function, measured as eGFR, and the zonulin concentration and were thus able to confirm the finding recently reported by Dschietzig et al 14 In this study, which was conducted in a special group of patients with an auto matic implantable cardioverter/ defibrillator, the authors had described such a correlation for the first time, deducing that the low zonulin concentration associated with impaired renal function results from the depletion of zonulin with the urine. We were indeed able to determine a significantly nega tive correlation between the serum zonulin concentration and the extent of proteinuria measured as UACR in the urine.…”
Section: Discussionsupporting
confidence: 91%
“…Zonulin is considered to be a valid biomarker of tight junction integrity of the gut in various diseases 22 , 23 . In ESRD elevated serum zonulin levels have been demonstrated by others and linked to inflammation and metabolic diseases 24 , 25 . No data on faecal zonulin or calprotectin levels in ESRD could be found in literature.…”
Section: Discussionmentioning
confidence: 89%
“…A previous study had shown a positive relationship between LPS and zonulin in T2DM [ 42 ]. Thus, increased zonulin levels allow more gut bacterial endotoxins and metabolites to cross the gut–membrane blood barrier into the circulatory system [ 43 , 44 ].…”
Section: Discussionmentioning
confidence: 99%